Development Of Augmented Reality Arabic For Islamic Tourism: Sustainable Education Need Analysis - Jaffar, Mohammad Najib; Ab Rahman, Azman; Abdul Hamed, Kirembwe Rashid; Ahmad, Mohammad Imran; Ritonga, Mahyudin; Noor Azam, Muhammad Harith (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study explored the need for analysis for development with integrated sustainable tourism education (STE)to enhance Islamic Tourism (IT) experiences in the region. The analysis scope included Tourists' perception of Augmented Reality (AR) usage, business owners' perception of (AR) usage, (AR) Application Content, and (AR) Application Interface and function. The questionnaire, descriptive statistics and purposive sampling procedures were used. The sample size n=20 of Malaysian and Indonesian Muslim tourists participated in the study. The findings supported an (AR) development embedded with (STE) for (IT). They predicted a positive impact of (AR) on (IT)and (STE) industries.